Phosphatidylserine Is Required for the Normal Progression of Cell Plate Formation in Arabidopsis Root Meristems. (16th June 2021) - Yamaoka, Yasuyo; Shin, Seungjun; Lee, Yuree; Ito, Masaki; Lee, Youngsook; Nishida, Ikuo
Abstract: Phosphatidylserine (PS) is involved in various cellular processes in yeast and animals. However, PS functions in plants remain unclear. In Arabidopsis, PS is relatively enriched in flower and root tissues, and the genetic disturbance of PS biosynthesis in phosphatidylserine synthase 1 ( PSS1 )/ pss1 heterozygotes induces sporophytic and gametophytic defects during pollen maturation. This study functionally characterized PS in Arabidopsis roots and observed that pss1 seedlings exhibited a short-root phenotype by reducing the meristem size and cell elongation capacity. Confocal microscopy imaging analyses of PS with GFP-LactC2 and the endocytic activity with FM 4-64 revealed that although GFP-LactC2 (or PS) was localized in the plasma membrane and endocytic membranes, the lack of PS in pss1 roots did not affect the constitutive endocytosis. Instead, a fluorescence imaging analysis of the cytokinetic phases in the dividing zone of pss1-2 roots revealed a significant delay in telophase progression, requiring active cargo vesicle trafficking for cell plate formation. Confocal microscopy imaging analysis of transgenic GFP-LactC2 root cells with developing cell plates indicated that GFP-LactC2 was localized at the cell plate. Moreover, confocal microscopy images of transgenic pss1-2 and PSS1 roots expressing the cell plate-specific syntaxin construct ProKNOLLE:eGFP-KNOLLE showed abnormal cell plate development in pss1-2 ProKNOLLE:eGFP-KNOLLE roots. These results suggested that PS is required for root cytokinesis, possibly because it helps mediate the cargo vesicular trafficking required for cell plate formation.